Penerapan Metode Failure Mode and Effect Analysis (FMEA) dan Six Sigma - Kusuma, Mukhlis Yoga; Rolliawati, Dwi; Subhan Nooriansyah (STMIK Amika Soppeng, 2024)
Putra Delta is a company located in Sidoarjo, East Java. Putra Delta's products are school attributes and uniforms that are marketed online, one of which is through e-commerce. The results of this study through several instruments, namely observation, interviews, and literature studies. The results of the interview from the owner of Putra Delta are that there are still many production defects in Putra Delta, which have an impact on service quality and affect the level of customer satisfaction with the Company. This study aims to analyse the application of the Failure Mode and Effect Analysis (FMEA) and Six Sigma methods in improving service quality at Putra Delta, a company engaged in school attributes and uniforms. In the context of growing e-commerce, companies are faced with a huge challenge to improve product and service quality to meet customer expectations. The defect frequency data obtained for 12 months shows that the production defect rate is still high, with a significant Defects Per Million Opportunities (DPMO) value. Through the FMEA method, various failure modes that could potentially occur in the production process were identified, as well as prioritising corrective actions based on the Risk Priority Number (RPN). The results of the analysis showed that the combined application of FMEA and Six Sigma not only successfully reduced product defects, but also improved operational efficiency and customer satisfaction. The findings emphasise the importance of an integrated quality control strategy in maintaining a company's reputation in a competitive market.